A Study of Efficiency and Economic Value of Grade Separated Construction Project: Case Study of Grade Separated Without Ramp across The Sri Ayutthaya Intersection Bangkok - Rachata Bilee; Jumrus Pitaksringkarn (Engineering and Technology Horizons, 2024)
This research was conducted to analyze the efficiency and economic value of grade separated construction projects in a large city due to heavy traffic volumes. This is consistent with the current situation where traffic volumes are continually increasing. In order to reduce fuel consumption, accidents and travel time. In this research, the efficiency and economic value of grade separated without ramp across Sri Ayutthaya intersection will be studied, Bangkok (Thailand), is considered in the form of an underpass through the intersection by using the VISSIM program to create and develop micro simulation traffic models. Then, the economic cost-benefit analysis of the project is evaluated by considering the economic worthiness of the project from a comparison between the case with the project and without the project. The economic worthiness of the project is analyzed by using Net Present Value (NPV), Benefit-Cost Ratio (B/C ratio) and Internal Rate of Return (IRR). From the results of this study, it was found that after developing the current area, which is a ground level intersection into an underpass. Traffic at intersections will be more efficient. And helps reduce traffic congestion at intersections. This is because the average delay of each type of vehicle decreased after the project. Performance measures at intersections can be summarized as the average vehicle delay in the project start year (2027) for motorcycles decreased from 364.48 seconds/vehicle to 85.93 seconds/vehicle, passenger cars decreased from 369.35 seconds/vehicle to 78.42 seconds/vehicle, trucks decreased from 282.19 seconds/vehicle to 78.96 seconds/vehicle, and buses decreased from 420.47 seconds/vehicle to 65.07 seconds/vehicle. And it can be concluded that the project of grade separated construction in the form of an underpass across Sri Ayutthaya Intersection. It is economically worthwhile and suitable for investment. Because the net present value (NPV) in the 15th year of the project (2041) is equal to 1,752.18 million baht, which is greater than 0, the benefits-costs ratio (B/C Ratio) in the 15th year of the project (2041) is equal to 3.61, which is greater than 1, and the internal rate of return (IRR) at the 15th year of the project (2041) is equal to 42%, which is greater than 12%.
Keywords: Urban Transport Systems Analysis